Deveploment of Onion Crackers Business with Product Labeling Strategy to Improve Marketing During Covid-19 - Rahmawati, Yunaita; Andriani, Sovi (Civiliza Publishing, 2024)
This study aims to identify the strengths, weaknesses, opportunities and treats of the onion shrimp cracker business in Tanjungsari Village, Jenangan District, Ponorogo Regency, then make a marketing strategy for the onion shrimp cracker business in the local village. The strategy that will be carried out is by increasing the product table which was originally only a patch on cracker wrappers, now turned into a color paper label that can attract buyers’ interest. Not only that to be able to increase sales of prawn crackers, it can also be done by increasing marketing by selling them through digital marketing facebook. The data obtained are sourced directly from prymary data, namely throught direct interviewsand involving direct conditions directly in the field. Based on the result of research and internal and external factors, it shows that the cracker business in Tanjungsari Village, Jenangan District, Ponorogo Regency hus been running for approximately 25 years, with a fairly affordable price, already has its own label and has been registered with PIRT. Processed products that only produce in raw form, in terms of size of crackers there are only large and medium sizes. For the treath, competitions have the same type of business, namely the onion shrimp crackers business, besides that there are also other things, namely weather and climate, as well as the price of ingredients standard that sometimes goes up high. For the marketing strategy og the onion prawn cracker business in the Tanjungsari Village, Jenangan District, Ponorogo Regency the right one is not only by selling it directly but also online so that its reach can be weader.